Pengelolaan Kelas Dalam Pembelajaran Pendidikan Agama Islam - Muadzah, Alya; Abdurrohim; Mustofa, Taufik; pengelola, pengelola (STAI Ihyaul Ulum Gresik, 2024)
Classroom management is the effort or effort of the teacher in creating and maintaining a good learning environment, so that learning runs in a conducive manner. The learning environment itself is one of the important factors in education, because the learning environment is very influential in the formation of mindsets, attitudes, personality and stages in development. By creating a conducive and effective learning environment, the teaching materials that will be delivered by the teacher can be conveyed properly. This is because the teaching and learning process is fun. The importance of a teacher in managing the classroom environment is to achieve educational success, which can give birth to students who uphold discipline. Therefore, in addition to the teacher managing the class, the teacher also needs to provide discipline to students. The purpose of this study was to find out how the management of the learning environment and the discipline of children was carried out by Islamic Religious Education teachers at SDN Panyingkiran 1. The research method used was a qualitative approach with a type of field research (Field Research) in which the researcher conducted direct observations and interviews. . The results of the study show that the creation of a good learning environment can produce students who have a disciplined attitude, so that educational success is achieved.